Endometrial Stem/Progenitor Cells–Their Role in Endometrial Repair and Regeneration - Cousins, Fiona L.; Filby, Caitlin E.; Gargett, Caroline E. (Frontiers in Reproductive Health, 2022)
The human endometrium is a remarkable tissue, undergoing approximately 450 cycles of proliferation, differentiation, shedding (menstruation), repair and regeneration over a woman’s reproductive lifespan. Post-menstrual repair is an extremely rapid and scar-free process, with re-epithelialization of the luminal epithelium completed within 48 hours of initiation of shedding. Following menstruation, the functionalis grows from the residual basalis layer during the proliferative phase under the influence of rising circulating estrogen levels. The regenerative capacity of the endometrium is attributed to stem/progenitor cells which reside in both the epithelial and stromal cell compartments of the basalis layer. Finding a definitive marker for endometrial epithelial progenitors (eEPCs) has proven difficult. A number of different markers have been suggested as putative progenitor markers including, N-cadherin, SSEA-1, AXIN2, SOX-9 and ALDH1A1, some of which show functional stem cell activity in in vitro assays. Each marker has a unique location(s) in the glandular epithelium, which has led to the suggestion that a differentiation hierarchy exists, from the base of epithelial glands in the basalis to the luminal epithelium lining the functionalis, where epithelial cells express different combinations of markers as they differentiate and move up the gland into the functionalis away from the basalis niche. Perivascular endometrial mesenchymal stem cells (eMSCs) can be identified by co-expression of PDGFRβ and CD146 or by a single marker, SUSD2. This review will detail the known endometrial stem/progenitor markers; their identity, location and known interactions and hierarchy across the menstrual cycle, in particular post-menstrual repair and estrogen-driven regeneration, as well as their possible contributions to menstruation-related disorders such as endometriosis and regeneration-related disorder Asherman’s syndrome. We will also highlight new techniques that allow for a greater understanding of stem/progenitor cells’ role in repair and regeneration, including 3D organoids, 3D slice cultures and gene sequencing at the single cell level. Since mouse models are commonly used to study menstruation, repair and regeneration we will also detail the mouse stem/progenitor markers that have been investigated in vivo.